Reduction of Metal Density of Iron (Fe) and Natrium Minerals (Na) in Boring Water Using Rubber Fruit Sheets Active Archoic - Zul Alfian; Uly Ashari (Talenta Publisher, 2024)
Activated carbon is a highly popular adsorbent for the absorption of metal ions. Lignocellulosic materials can be used to produce activated carbon, which is both renewable and abundant, as well as being cost-effective. The objective of this research is to investigate the reduction of iron (Fe) and sodium (Na) levels in the artesian well by utilizing activated carbon made from rubber shells. The materials utilized include rubber shells, a solution containing 10% H3PO4 (phosphoric acid), water from an artesian well, and distilled water (aquadest). The carbonization process was conducted at 300Âº C for 1 h, using an adsorbent size of 120 mesh. In addition, chemical activation was performed using a 10% H3PO4 solution for 24 h, followed by physical activation through heating in a furnace at a temperature of 500ÂºC for 1 hour. The acquired activated carbon is utilized for the absorption of Fe and Na. The activated carbon was characterized using X-ray diffraction (XRD), and the concentration of Fe and Na minerals was determined using an Atomic Adsorption Spectrophotometer (AAS). The results indicated a reduction of 97.9% in the concentration of iron (Fe) and a decrease of 90.01% in sodium (Na) levels.